Artisan entrepreneurship - Ratten, Vanessa; Jones, Paul; Braga, Vitor; Parra-López, Eduard (Emerald Publishing Limited, 2022)
Increased interest in handicrafts has led to more people becoming artisans both as a hobby and a business activity, making Artisan Entrepreneurship a growing phenomenon. This has been particularly relevant during the COVID-19 crisis in which individuals and communities began engaging with more bespoke crafting at home. This book focuses on these practices from different perspectives including the art, cultural and social sectors, thereby highlighting the emerging new types of artisan activity that preserve cultural elements while incorporating emerging technologies like social media. This volume analyses artisan entrepreneurship using different approaches including at an individual, group and societal point of view providing a better understanding about how these handicraft workers contribute to societal wellbeing and aid cultural heritage preservation for future generations. Each chapter of this book looks at these practices in a different way, enabling the practical and theoretical significance of artisan entrepreneurship to emerge and presenting a holistic understanding of artisan entrepreneurship in different contextual settings. Artisan Entrepreneurship provides a unique way in which to understand an important type of enterprise that has been neglected but recently had a resurgence. This book provides a fundamental contribution to the field of artisan entrepreneurship.